Pemberdayaan Masyarakat Melalui Budidaya Pembesaran Ikan Lele dengan Sistem Bioflo - Andri Irawan; Rachmat A.P. Parukka; Lindon R. Pane; Jeremias R. Tuhumena; Silas T. Redu (Universitas Pahlawan Tuanku Tambusai, 2023)
The problem faced by the Coal Fish Farm catfish farming business group is that they are still cultivating using conventional systems. Another factor is the lack of knowledge and skills possessed by business members on how to cultivate catfish, such as feeding methods and maintain good water quality. The purpose of the service is to provide education to business groups through cognitive aspects about the benefits of cultivating catfish with the biofloc system, increasing independence in the economy, and being able to compete with the market. The method is carried out by surveying target partners to identify problems, needs, socialization, training and mentoring. The result of this service is increased knowledge and understanding of community in implementing the catfish rearing biofloc system. In addition, the success of community empowerment can be seen from the increase in cultivation group members from the surrounding village community.